2015
DOI: 10.1111/mec.13331
|View full text |Cite
|
Sign up to set email alerts
|

On the relative roles of background selection and genetic hitchhiking in shaping human cytomegalovirus genetic diversity

Abstract: A central focus of population genetics has been examining the contribution of selective and neutral processes in shaping patterns of intraspecies diversity. In terms of selection specifically, surveys of higher organisms have shown considerable variation in the relative contributions of background selection and genetic hitchhiking in shaping the distribution of polymorphisms, though these analyses have rarely been extended to bacteria and viruses. Here, we study the evolution of a ubiquitous, viral pathogen, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 72 publications
(135 reference statements)
1
40
0
Order By: Relevance
“…All of these factors, except the distribution of fitness effects, have been studied and inferred in HCMV intrahost populations (10)(11)(12). The DFE characterizing HCMV intrahost populations is inferred here using two methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these factors, except the distribution of fitness effects, have been studied and inferred in HCMV intrahost populations (10)(11)(12). The DFE characterizing HCMV intrahost populations is inferred here using two methods.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters included the mean effective population size (N e ), as well as mutation and recombination rates. Further, four additional sets of simulations were performed, following previous reports suggesting that background selection and demography alter the patterns of polymorphism of in vivo HCMV populations (10). These simulations are identified as strong constraint, demography, demography/strong constraint, and demography/strong and weak constraint.…”
Section: Resultsmentioning
confidence: 99%
“…This could be indicative of mixed viral populations or changes in polymerase fidelity (24,22). As in congenital HCMV infections (25,28,30), these data suggested that patients experiencing neonatal infection with HSV-2 may harbor mixed or diverse viral populations that are distinct from those observed in adult infections. These minor genotypes may be selected or genetically isolated in particular niches (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…Each isolate was cultured once as part of the diagnostic process with expansion only for the experiments shown here. Although this is a relatively small group of samples due to the constraints discussed previously, it is the largest group of neonatal HSV samples ever compared genotypically or phenotypically, and is similar in size to prior studies of HCMV-infected neonates (25)(26)(27)(28)(29)(30).…”
Section: Neonatal Hsv-2 Samples Represent a Diverse Clinical Populationmentioning
confidence: 82%
See 1 more Smart Citation